Influenza virus infections in patients with malignancies - characteristics and outcome of the season 2014/15: a survey conducted by the Infectious Diseases Working Party (AGIHO) of the German Society of Haematology and Medical Oncology (DGHO) - Hermann, Beate; Giesen, Nicola (European journal of clinical microbiology & infectious diseases, 2017)
Influenza virus infections (IVI) may pose a vital threat to immunocompromised patients such as those suffering from malignancies, but specific data on epidemiology and outcome in these patients are scarce. In this study, we collected data on patients with active cancer or with a history of cancer, presenting with documented IVI in eight centres in Germany. Two hundred and three patients were identified, suffering from haematological malignancies or solid tumours; 109 (54 %) patients had active malignant disease. Influenza A was detected in 155 (77 %) and Influenza B in 46 (23 %) of patients (genera not determined in two patients). Clinical symptoms were consistent with upper respiratory tract infection in 55/203 (27 %), influenza-like illness in 82/203 (40 %), and pneumonia in 67/203 (33 %). Anti-viral treatment with oseltamivir was received by 116/195 (59 %). Superinfections occurred in 37/203 (18 %), and admission on an intensive care unit was required in 26/203 (13 %). Seventeen patients (9 %) died. Independent risk factors for death were delayed diagnosis of IVI and bacterial or fungal superinfection, but not underlying malignancy or ongoing immunosuppression. In conclusion, patients with IVI show high rates of pneumonia and mortality. Early and rapid diagnosis is essential. The high rate of pneumonia and superinfections should be taken into account when managing IVI in these patients.